Probing the superconducting gap symmetry of α − PdBi 2 : A penetration depth study - Mitra, Sreemanta (2017)
We report measurements of the in-plane London penetration depth λ in single crystals of the α−PdBi2 superconductor—the α-phase counterpart of the putative topological superconductor β−PdBi2, down to 0.35 K using a high-resolution tunnel-diode-based technique. Both λ and superfluid density ρs exhibit an exponential behavior for T≤ 0.35Tc, with Δ(0)/kBTc ∼ 2.0, ΔC/γTc ∼ 2.0, and λ(0) ∼ 140 nm, showing that α−PdBi2 is a moderately coupling, fully gapped superconductor. The values of Δ(0) and ΔC/γTc are consistent with each other via strong-coupling corrections.